Killing of Giardia lamblia by cryptdins and cationic neutrophil peptides. - Aley, S B (1994)
Antimicrobial polypeptides such as the defensins kill a wide range of organisms, including bacteria, fungi, viruses, and tumor cells. Because of the recent finding that intestinal defensins, also known as cryptdins, are synthesized by the Paneth cells of the small intestinal crypts and released into the lumen, we asked whether defensins and other small cationic antimicrobial peptides could kill the trophozoites of Giardia lamblia, which colonize the small intestine. Four mouse cryptdins, two neutrophil defensins (HNP-1 [human] and NP-2 [rabbit]), and the unique tryptophan-rich bovine neutrophil polypeptide indolicidin each had some antigiardial activity against trophozoites in vitro. Cryptdins 2 and 3, indolicidin, and NP-2 each reduced viability by more than 3 log units in 2 h, and killing by all peptides was dose and time dependent. Exposure of trophozoites to peptides frequently resulted in cell aggregation and dramatic changes in morphology. The mechanism of binding and lysis appeared to involve charge interactions, since 150 mM NaCl as well as millimolar levels of Ca2+ and Mg2+ inhibited killing by most of the peptides. Our studies show that G. lamblia is sensitive to defensins and indolicidin and suggest that these small polypeptides could play a role in nonimmune host defenses.